2015
DOI: 10.1159/000433565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxygen Supplementation Status as a Risk Factor Associated with the Development of Severe Retinopathy of Prematurity

Abstract: Purpose: The effects of oxygen supplementation status and other clinical risk factors on the development of severe retinopathy of prematurity (ROP) were evaluated. Methods: Clinical records of 143 newborn infants with a gestational age of 32 weeks or less were reviewed. Severe ROP was diagnosed when photocoagulation due to progression to stage 3 was identified or when ‘plus disease' developed. The factors were evaluated with univariate and multivariate logistic regression analyses between the groups with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…In the present study, the average gestational age and birth weight in the group without ROP were higher than the group with ROP. These results were consistent with the findings of other studies ( 19 ). Also in this study, the mean of oxygen duration and oxygen concentrations in the group with ROP was higher than the group without ROP.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the average gestational age and birth weight in the group without ROP were higher than the group with ROP. These results were consistent with the findings of other studies ( 19 ). Also in this study, the mean of oxygen duration and oxygen concentrations in the group with ROP was higher than the group without ROP.…”
Section: Discussionsupporting
confidence: 94%
“…Gestational age, birth weight, duration of oxygen supplementation, duration of directional positive air pressure and maximum fraction of inspiratory oxygen (FiO2) were significantly associated with severe ROP in the univariate analyses. In the multivariate analysis, a longer duration of oxygen supplementation and a higher maximum FiO2 were revealed as significant risk factors associated with severe ROP ( 12 ). Park SH at all.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] It has been suggested that the incidence of and risk factors for ROP may also differ in different regions due to differences in perinatal care, ethnicity, and screening criteria. [18][19][20][21][22][23][24][25] The aim of this study was to analyze the risk factors and the incidence of ROP among VLBW preterm Chinese infants in Hong Kong.…”
mentioning
confidence: 99%